The role of developmental experience in the career development of fire chiefs in the United States - Jones, Warren D., author; Feller, Richard, advisor; Grosse, Larry, advisor; Banning, James, committee member; Littrell, John, committee member (Colorado State University. Libraries, 2007)
This study examined the career experiences of fire chiefs. It goes beyond an examination of the traditional technical competencies and time in position elements of a fire chief's career development by focusing on specific experiences that produced change in their leadership and management behaviors. These are called developmental experiences. The audience for this study is fire chiefs, those that aspire to this position and other fire service professionals seeking to better understand the career development of fire chiefs. The research approach used was qualitative and the methodology was multiple case study using narrative analysis technique. Developmental experience has emerged as an experiential learning strategy that improves a leader's ability to adapt to and positively influence organizational success under conditions of change. The literature indicates that positive changes in leadership and management behaviors derived from developmental experience come from challenging on-the-job experiences, which result in personal learning and changes in leadership and management behaviors. The results of this study indicate that the 14 participants described nine common themes that met the definition of developmental experience in accordance with the Center for Creative Leadership developmental experience model. The participants furthermore described 26 examples of personal learning in seven developmental experience themes and 23 examples of changes in leadership and management behavior in four developmental experience themes. Two developmental experience themes, (1) the first fire chief and (2) hardship produced the strongest learning and change in leadership and management behaviors. The results of this study challenge the conventional fire service career development systems in place today. It recommends that (1) developmental experience opportunities be made available to fire service personnel much earlier in their careers, especially for those who display leadership talent; (2) that more focus be placed on leadership and management experience in the early career; (3) that learning from hardship be incorporated into leadership development; and (4) that more opportunities be provided to learn political skills outside the confines of the internally focused fire service world.